2013
DOI: 10.1016/j.pedhc.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnography of the Culture of Pain in a Non-Pediatric Emergency Department

Abstract: Rationale for the Study: Despite the exponential growth in pharmacological and nonpharmacological methods for the treatment of pediatric procedural pain there remains a gap between available interventions and actual practice in the emergency department clinical setting. Researchers have recommended the examination of unit culture since culture is proposed to be a major factor that affects the implementation of pain management practices. Method:Ethnography was employed to gain access to the beliefs and practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 175 publications
(430 reference statements)
0
1
0
Order By: Relevance
“…However, other studies have reported that physicians and nurses document pain assessment without asking patients about pain, suggesting that documented scores may reflect staff judgment rather than patient report. 43,44 Ambiguity within current guidelines about whether pain scores should be documented according to patient report or a combination of patient report and staff judgment suggests that practice will be variable.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported that physicians and nurses document pain assessment without asking patients about pain, suggesting that documented scores may reflect staff judgment rather than patient report. 43,44 Ambiguity within current guidelines about whether pain scores should be documented according to patient report or a combination of patient report and staff judgment suggests that practice will be variable.…”
Section: Discussionmentioning
confidence: 99%